European Investment Advisory Hub Report 2021 - European Investment Bank (2022)
"Funded and managed by the European Commission and the European Investment Bank, the European Investment Advisory Hub helps identify, prepare and implement sustainable investment projects across Europe. Since its launch, the European Investment Advisory Hub has received more than 2 500 direct requests for in-depth support. In 2021, less-developed, so-called cohesion countries submitted the greatest number of requests. The European Investment Advisory Hub's main goal is to give promoters a comprehensive and bespoke advisory package, which includes information and guidance via our website, tailored assistance to develop and implement investment projects and platforms, and light advisory support when projects just need a little extra push to get up and running. As the 2021 report shows, the road to recovery is looking increasingly green and digital as the technological advances spurred on by the COVID-19 pandemic are harnessed and paired with climate-minded investments."